Beneficial effects of native phosphate solubilizing bacteria on peanut (Arachis hypogaea L) growth and phosphorus acquisition - Anzuay, María Soledad (2015)
This study analyses the effect of inoculation of native phosphate solubilizing bacteria on peanut (Arachis hypogaea L.) growth and phosphorus acquisition. Peanut plants were inoculated individually with 18 native phosphate solubilizing bacteria in microcosm studies using a low content P soil from the producing area. Survival of inoculated bacteria in soil at the end of the experiment was determined by streaking serial dilutions of dry soil samples and subsequent rep-fingering analysis of the colonies. The ability of peanut plants to increase P levels without bacteria was determined in hydroponic culture. The results obtained indicated that inoculation of native phosphate solubilizing bacteria on peanut seedlings led to an increase in at least one of the plant growth parameters analyzed. The beneficial effect of bacteria inoculation was mainly observed in aerial organs of peanut plants. Inoculation of Serratia sp. J260, Enterobacter sp. J33, Acinetobacter sp. L176, Enterococcus sp. L185, Enterococcus sp. L191 and Bacillus sp. L55 on peanut plants led to an increase in plant or soil P content. Plant assay in hydroponic conditions indicated that peanut plants growing with tricalcium phosphate were able to release soluble P into the growth medium reaching values similar to those of plants growing with available P. The beneficial effects of the bacteria analyzed in this study and their ability to survive encourage us to consider them for the production of a potential P-bioinoculant for peanut crops.